2020
DOI: 10.1365/s41056-020-00047-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategic framework for resident’s participation in housing provision in Akure, Southwest Nigeria

Abstract: Purpose This paper furthered the work done by Choguill (1996) in developing a framework for community participation in housing provision for Akure, Southwest Nigeria. The study tests the ladder for suitability in the City, and accounted for residential satisfaction as an important result of resident’s participation, which was not considered in Choguill’s ladder. Design/methodology/approach The paper reports a cross-sectional doctoral research on residents’ participation in housing in Akure. The data for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…With the move from blueprint to more collaborative urban planning, governments have turned towards incorporating residents into urban regeneration projects. Relatedly, previous studies on resident participation and residential satisfaction have found that the more residents are included in decision-making processes within their residential environment, the more satisfied they will be living there (Ammar et al, 2013;Aigbavboa & Thwala, 2013;Fakere et al, 2020). Drawing from Wilcox's Ladder of Participation (1999), four phases of public participation, resident participation in urban regeneration projects need to be more than a 'superficial consultation' where residents are consulted on the implementation of evaluative phases of the projects, which produces long-term issues within the community.…”
Section: Residential Participationmentioning
confidence: 99%
“…With the move from blueprint to more collaborative urban planning, governments have turned towards incorporating residents into urban regeneration projects. Relatedly, previous studies on resident participation and residential satisfaction have found that the more residents are included in decision-making processes within their residential environment, the more satisfied they will be living there (Ammar et al, 2013;Aigbavboa & Thwala, 2013;Fakere et al, 2020). Drawing from Wilcox's Ladder of Participation (1999), four phases of public participation, resident participation in urban regeneration projects need to be more than a 'superficial consultation' where residents are consulted on the implementation of evaluative phases of the projects, which produces long-term issues within the community.…”
Section: Residential Participationmentioning
confidence: 99%
“…1. Akure was chosen for this study because of prevalent self-help phenomenon in the city as well as poor state of housing infrastructure (Lawal & Baosrun, 2015;Fakere, et al, 2020a). The study utilised the questionnaire survey tool and physical observations (shown in pictures) as means of data collection for the research.…”
Section: International Journal Of Community Development and Managemen...mentioning
confidence: 99%
“…This phenomenon has led many communities in the country to resort to self-help efforts to manage the problem. According to Choguill (1996) and Fakere, et al (2020a), self-help is the lowest level of community participation. In this level, the community members come together through decision making and mutual financial contributions, to provide or maintain the infrastructure within their neighbourhoods, with low success rates, especially when they do not receive any outside support from government or non-governmental organizations (Fakere, et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local governments in both the UK and the USA conduct regular tenant satisfaction surveys to ensure that households are satisfied with the provided housing and its services". Furthermore, Fakere et al (2020) shared that "the United Nations Rio Summit of 1992 (Principle 10) stressed the need for people to participate in housing developments. This is because of its potential to enhance residents' quality of life since such developments are more likely to meet their needs when they are involved in the process.…”
Section: Introductionmentioning
confidence: 99%